2022
DOI: 10.5530/pj.2022.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic, Flavonoids, and Carotenoids Content and Anti- Obesity Activity of Purslane Herb (Portulaca oleracea L.) Ethanol Extract

Abstract: Objective: The current study aims to determine total flavonoid content (TFC), total phenolic content (TPC), and total carotenoid content (TCC) of ethanolic extract of Purslane (Portulaca oleraceae L.). Material and Method: Herb of Purslane (Portulaca oleraceae L.) was extracted using ethanol. Determination of total flavonoid content (TFC), total phenolic content (TPC), and total carotenoid content (TCC) The method used spectrophotometer UV-VIS by the used standard curve to compare the total content by linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
3
Order By: Relevance
“…This plant is of great importance because of containing many compounds that are beneficial to human health (prevention and treatment) as an anti-metabolite (the condition of the metabolic syndrome in the body), works on many pathways in the metabolic syndrome, such as reducing fats, blood sugar in diabetes (type ii), body weight, and total cholesterol [32]. A study also confirmed that the purslane plant is a good source of flavonoids, phenols, and carotenoids and that the ethanol extract of purslane has the potential as an anti-obesity [29]. [30] has mentioned that his studies have proven that the purslane plant is a rich source of chlorophyll, carotene, and anthocyanin, meaning that it may become a cheap source for the treatment of many diseases…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This plant is of great importance because of containing many compounds that are beneficial to human health (prevention and treatment) as an anti-metabolite (the condition of the metabolic syndrome in the body), works on many pathways in the metabolic syndrome, such as reducing fats, blood sugar in diabetes (type ii), body weight, and total cholesterol [32]. A study also confirmed that the purslane plant is a good source of flavonoids, phenols, and carotenoids and that the ethanol extract of purslane has the potential as an anti-obesity [29]. [30] has mentioned that his studies have proven that the purslane plant is a rich source of chlorophyll, carotene, and anthocyanin, meaning that it may become a cheap source for the treatment of many diseases…”
Section: Introductionmentioning
confidence: 88%
“…It is clear for this trait that the local vegetables under study are generally fiber-rich (for the higher value of the red radish sprouts or the lower value of the brown mustard sprouts). In a study in India related to producing microgreens from several vegetable seeds, including red radish and brown mustard, soaked in distilled water for 24 hours and harvested 6 to 13 days after planting, [29] found that the fiber percentage in the red radish and mustard was 2.86 and 2.6% respectively. This result may explain the roughness of the local radish leaves (especially in the adult leaves), which differ significantly from the foreign varieties to the naked eye.…”
Section: Raw Fiber Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these antioxidant compounds can also maintain the organ health due to their antimetabolic activity. 22,27,43 The presence of antioxidants in P. olaracea is associated with cellular oxidative stress. Oxidative stress is caused by reactive oxygen species that trigger cell and tissue damage, especially liver tissue.…”
Section: Pathogenesis and Pathophysiology Of Metabolic Syndromementioning
confidence: 99%
“…7,22,43,44 Concurrently with this decrease, there was an increase in HDL-C (high density lipoprotein-cholesterol) which resulted in a decrease in body fat and weight loss. 3,22,27…”
Section: Pathogenesis and Pathophysiology Of Metabolic Syndromementioning
confidence: 99%